Utilizing the internet of things (IoT) to develop a remotely monitored autonomous floodgate for water management and control - Hajjaj, Sami Salama Hussen; Hameed Sultan, Mohamed Thariq; Moktar, Muhammad Hafizuddin; Lee, Seng Hua (MDPI, 2020)
In recent years, floods have increased in frequency and intensity, causing tremendous hardship. In badly affected regions, mostly the rural areas, Weir-type floodgates are the only measure against floods. However, these manually operated gates are numerous and scattered over vast areas. This makes flood mitigation efforts very challenging, which causes severe devastation. Current solutions to automate the floodgates are expensive, black-boxed, and focused on individual gates. In this paper, we present a Centralized Flood Monitoring and Coordination System developed through the Internet of Things (IoT) and other open-source technologies. For this work, we developed a working prototype of an autonomous floodgate that opens/closes according to the level of water. We also developed the required program to allow the gate controller to publish its data through the IoT gateway to the cloud. The data was then captured and viewed on a number of IoT clients, both for individuals and groups of floodgates, in real time. The developed system proved successful as the autonomous gates were monitored remotely through the established IoT framework, with room for future development and improvement. This paper serves as a proof of concept and a preparation for real, on-site implementation of the IoT-floodgates.